Eutectic Mixtures Based on Oleic Acid and Pulsed Electric Fields: A Strategy for the Extraction of Astaxanthin from Dry Biomass of Xanthophyllomyces dendrorhous - Javier Marañés; Alejandro Berzosa; Fernando Bergua; Javier Marín-Sánchez; Javier Raso; Manuela Artal (Foods)
The use of astaxanthin (AST) is expanding from its origins as a food coloring to health-related applications. This paper evaluates the efficiency of its extraction from dried Xanthophyllomyces dendrorhous using two combined and consecutive techniques. First, cell membrane permeation is achieved with the application of pulsed electric fields (PEFs). Solid–liquid extraction is then performed with hydrophobic eutectic solvents (hESs) prepared by mixing components of essential oils (linalool, l-menthol, eugenol, geraniol, cinnamyl alcohol, or thymol) and oleic acid. The hESs were characterized by measuring of several thermophysical properties at 25 °C and 0.1 MPa. An initial screening was performed to choose the best solvent and the extraction conditions (composition, extraction time, and temperature) were evaluated using the response surface methodology. The results showed the importance of the electroporation as a preliminary step to the extraction. The more hydrophobic and less compact the hES, the more effective the solvent. Thus, the equimolar mixture of l-menthol and oleic acid achieved an efficiency of 77% for untreated biomass, 83% for that treated with PEF, and 92% for that treated with PEF and later incubated. Molecular dynamics simulations demonstrated the importance of the hydrophobic interactions between AST and the components of the best solvent.